Targeting hypoxia-inducible factor 1α in chronic graft-versus-host disease to enhance graft-versus-leukemia responses: implications for nanotherapeutics - Wang, Yimin; Zhou, Fang (Frontiers in Immunology, 2025)
Chronic graft-versus-host disease (cGVHD), a severe complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT), arises from donor immune cell-mediated tissue damage, chronic inflammation, and fibrosis. Current therapies fail to adequately address fibrotic progression and heighten infection risks, underscoring the need for targeted strategies. Hypoxia-inducible factor-1α (HIF-1α), a pivotal regulator, emerges as a potential therapeutic target by orchestrating immunometabolic homeostasis, suppressing fibrosis, preserving gut microbiota balance, and retaining graft-versus-leukemia (GVL) effects. However, clinical translation necessitates overcoming challenges in tissue specificity and off-target effects. Smart nanodelivery systems hold promise for enhancing precision to enable localized HIF-1α pathway modulation. This review highlights the multidimensional roles of HIF-1α in cGVHD pathogenesis and proposes nanotherapeutic approaches to reconcile immunofibrotic imbalances, advancing a paradigm shift in cGVHD management while preserving GVL efficacy.